Strengthening Boss Fund Governance Through Accounting Standards-Based Assistance in Deli Serdang Regency - Yulita Triadiarti (Jurnal Pendidikan Indonesia, 2025)
This research aims to formulate an effective, transparent, and accountable BOS Fund management strategy, as well as to identify the need for technical assistance based on Government Accounting Standards (SAP) in Junior High Schools (SMP) in Deli Serdang Regency. The method used was mixed methods through a questionnaire survey to 62 school principals and treasurers, as well as interviews and Focus Group Discussions (FGD). The results of the study show that the majority of schools do not understand SAP thoroughly and still face obstacles in the preparation of transparent and accountable financial statements. The need for technical assistance is very high, especially in training in SAP-based report preparation, the use of reporting applications such as ARKAS, and strengthening digital literacy. This research resulted in the design of a training and mentoring model based on school needs that aims to improve managerial capacity and the quality of financial reporting. These findings reinforce the importance of institutional intervention and the development of information technology-based support systems. Thus, the right technical assistance strategy plays an important role in encouraging the realization of BOS Fund governance that is in line with the principles of public accountability and SAP implementation.